The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.32098/mltj.03.2022.09
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Connective Tissue Morphologic Characteristics in Runners. How Do They Relate with Running Biomechanics and Tendon Pathology? A Systematic Review

Abstract: Although the role of connective tissue in running injuries and biomechanics has been widely investigated, systematic reviews on this issue were rarely reported. The aim of this study is to systematically review the current literature regarding the morphological characteristics (i.e., cross-sectional area and thickness) of the main connective tissue of the lower limb in runners and its relationship with running biomechanics and tendon pathology. The main keywords used were: Achilles and patellar tendons, planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Our study also showed wider cross-section area (CSA) of running rats compared to control group. As mentioned in previous systematic review published at 2022 (21), tendon connective tissue involvement plays important role in Achilles tendinopathy pathogenesis. Wider CSA is formed as an adaptation towards repetitive overload.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study also showed wider cross-section area (CSA) of running rats compared to control group. As mentioned in previous systematic review published at 2022 (21), tendon connective tissue involvement plays important role in Achilles tendinopathy pathogenesis. Wider CSA is formed as an adaptation towards repetitive overload.…”
Section: Discussionmentioning
confidence: 89%
“…Normally repetitive overload induced increasing tenocyte and collagen fiber of tendon. But if the repetitive overload was excessive, collagen fiber formation would not be unable to keep up with tenocyte production and producing stiffer and wider tendon (21). Running the rats on the treadmill as an attempt to induce Achilles tendinopathy also increases several inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…No comparison with pathological (i.e., gait pathologies) or sport (i.e., runners) populations has been carried out here. Long-distance runners tend to show larger dimensions in terms of CSA and thickness in the PT, AT and PF given the amount of load supported by these tendons [28]. As it seems that a thicker PT significantly correlates with a longer R1, we might hypothesize that long-distance runners would exhibit longer R1 duration.…”
Section: Discussionmentioning
confidence: 97%